Illuminated Sasak Stories: A Bridge to English Language Learning - Muliani, Muliani; Hidayatullah, Heri; Qomariyah, Siti Syafi’atul (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2024)
This study seeks to enhance elementary school students’ appreciation of Sasak cultural heritage in Central Lombok, an area increasingly influenced by tourism and exposure to foreign cultures. Recognizing a need to prioritize local cultural education, this research introduces illuminated stories, created with the input of five English teachers who contributed traditional stories and games from their childhood. Using a Problem-Based Learning (PBL) approach, 20 students engaged with these stories, and their progress was assessed using a validated tool that measured both cultural knowledge and language proficiency. Preliminary results demonstrate improvements in studentsâ€™ engagement, cultural understanding, and language skills, highlighting the effectiveness of combining cultural education with PBL. These findings encourage further research with larger and more varied student groups to build on these promising outcomes.